Behavioral Evidence for Enhanced Processing of the Minor Component of Binary Odor Mixtures in Larval Drosophila - Chen, Yi-chun; Mishra, Dushyant; Gläß, Sebastian; Gerber, Bertram (Frontiers in Psychology, 2017)
A fundamental problem for taking decisions between mutually exclusive options is that the decision needs to be categorical although the properties of the options often differ but in grade. We developed an experimental handle to study this aspect of behaviour organization. Larval Drosophila were trained such that in one set of animals odour A was rewarded, but odour B was not (A+/B), whereas a second set of animals was trained reciprocally (A/B+). We then measured the preference of the larvae either for A, or for B, or for ‘morphed’ mixtures of A and B, that is for mixtures differing in the ratio of the two components. As expected, the larvae showed higher preference when only the previously rewarded odour was presented than when only the previously unrewarded odour was presented. For mixtures of A and B that differed in the ratio of the two components, the major component dominated preference behaviour– but it dominated less than expected from a linear relationship between mixture ratio and preference behaviour. This suggests that a minor component can have an enhanced impact in a mixture, relative to such a linear expectation. The current paradigm may turn out useful to understand how nervous systems generate discrete outputs in the face of inputs that differ but gradually.